Informaatiosektorin energian- ja sähkönkäyttö Suomessa; Energy and Electricity Consumption of the ICT-sector in Finland - Kari Hiekkanen; Timo Seppälä; Ilkka Ylhäinen (The Research Institute of the Finnish Economy (ETLA), 2020)
– The role of the digital technologies are becoming increasingly important in our day-to-day life. Digital technologies have become part of our social life as well as business operations across different industrial and public sectors. Because of digitalization the internet protocol and data traffic have been on the rise for several years. A few studies and estimates have been presented about the increasing future use of energy and electricity. Occasionally consumer behaviors have been claimed to be behind of these increases in electricity use.This report makes an effort to understand the energy and electricity consumption of the Finnish Information sector (ICT-sector) from 2011 until 2017. Additionally, we compare the Finnish electricity use to other Europe-an countries with similar data available. The findings of this study are partly inconsistent with those previously presented in terms of future energy and electricity use. Our report also shows that energy efficiencies of the information sector have not been retained while the internet protocol and data traffic have been increasing in both fixed and mobile networks
Keywords: L8; L82; L86; L94; 330; Information economy sector; ICT; IP traffic; Data use; Energy consumption; Electricity consumption